Mathematical model analyses on the effects of global temperature and forest cover on seasonal rainfalls: A Northern Thailand case study - Duangdai,E. (Elsevier, 2015)
© 2015 Elsevier B.V. In this work, an empirical mathematical model representing the relationship between global temperature, forest cover and seasonal rainfalls is constructed and validated using global temperature data for the years 1973-2010, Northern Thailand's forest area data for 1973-2008, and seasonal rainfall data for 1973-2011. The coefficient correlations of the model and the corresponding data are 0.8902, 0.9739 and 0.9751 respectively. Although there are some approximations and assumptions made throughout the analyses, statistical tests confirm that the proposed model can be used to predict the amount of rainfalls in the region. A case study on how government reforestation policy affects seasonal rainfalls is analyzed using the model modified to a solvable form. Three possible scenarios are created to predict possible outcomes of said policy. The results obtained show that under all scenarios, rainfalls increase in all seasons. Moreover, forest cover increase leads to more rainfall in the summer yet results in less rainfall in the other two seasons. The model can be modified and applied to predict rainfalls in other regions with similar topography and the climate after some statistical tests.